2017
DOI: 10.1186/s40880-017-0180-0
|View full text |Cite
|
Sign up to set email alerts
|

The loss-of-function mutations and down-regulated expression of ASB3 gene promote the growth and metastasis of colorectal cancer cells

Abstract: BackgroundAnkyrin repeat and SOCS box protein 3 (ASB3) is a member of ASB family and contains ankyrin repeat sequence and SOCS box domain. Previous studies indicated that it mediates the ubiquitination and degradation of tumor necrosis factor receptor 2 and is likely involved in inflammatory responses. However, its effects on oncogenesis are unclear. This study aimed to investigate the effects of ASB3 on the growth and metastasis of colorectal cancer (CRC).MethodsWe used next-generation sequencing or Sanger se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Polymorphisms in this member of the IL-1 superfamily were shown to be predictive of depression and anxiety through altered amygdala reactivity of threat perception in women but not in men ( Swartz et al , 2017 ). While the role of ASB family members is not well described ( Chung et al , 2005 ), one family member ASB3 has been shown to regulate responses to the pro-inflammatory cytokine tumor necrosis factor (TNF)-alpha by mediating the degradation of its receptor TNF-R2 ( Chung et al , 2005 ) and its gene expression is downregulated in colorectal cancer ( Du et al , 2017 ). The impact of stress-induced Asb1 expression on peripheral inflammation was further supported in our mouse model, where we observed strong correlation of Asb1 expression with expression of the IL-1B gene.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in this member of the IL-1 superfamily were shown to be predictive of depression and anxiety through altered amygdala reactivity of threat perception in women but not in men ( Swartz et al , 2017 ). While the role of ASB family members is not well described ( Chung et al , 2005 ), one family member ASB3 has been shown to regulate responses to the pro-inflammatory cytokine tumor necrosis factor (TNF)-alpha by mediating the degradation of its receptor TNF-R2 ( Chung et al , 2005 ) and its gene expression is downregulated in colorectal cancer ( Du et al , 2017 ). The impact of stress-induced Asb1 expression on peripheral inflammation was further supported in our mouse model, where we observed strong correlation of Asb1 expression with expression of the IL-1B gene.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was performed as previously described [24, 25]. Briefly, the cells mentioned above were collected and lysed in lysis buffer [24] and then concentrated by a BCA protein assay kit (Pierce Biotechnology, Rockford, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The migration ability of cell lines was assessed using a monolayer wound healing assay 45 . Briefly, cells were seeded in 6-well plates and grown to confluence overnight.…”
Section: Methodsmentioning
confidence: 99%